Hubungan Antara Karakteristik, Pengetahuan, Dan Sikap Dengan Keterampilan Peternak Sapi Perah Dalam Praktik Teat Dipping - Dwi Nor Wardiani; Siti Azizah (JURNAL RISET RUMPUN ILMU HEWANI, 2023)
Teat dipping is the activity of dipping a dairy cow’s teat into an antiseptic solution was prevent mastitis. Every dairy farmer has different knowledge, attitude and skills. This research to determine the correlation between characteristics, knowledge, and attitude with skills of dairy farmers in teat dipping practices using correlation with SPPS 26. The method used in this research is a descriptive quantitative survey. The study was conducted at KUD Tulus Bakti, Pagu, Kediri from 7 June to 5 September 2021. Respondents in this study were 30 members KUD Tulus Bakti and dairy farmer. The result show that the knowledge and the attitudes of the dairy farmer in this study were categorized as good, and the skills of the dairy farmer in the study were categorized as moderate. Characteristics based on age, education level, number of livestock and farming experience are related to the farmer's skill in teat dipping practice. There is a significant correlation between knowledge and skills of dairy farmer in the practice of teat dipping of KUD Tulus Bakti members, and the level of the correlation is moderate. There is a significant correlation between attitudes and skills of dairy farmer in the practice of teat dipping members of KUD Tulus Bakti, and the level of correlation moderate.